Triangulux - Uma proposta de jogo digital para o ensino de matemática - Pereira, Antônia Lília Soares (2023)
In this dissertation we present a proposal to develop an educational software for teaching mathematics, specifically a digital game, a pedagogical innovation that brings a script based on the life history of the "forest peoples". The research of qualitative approach, of applied purpose, presents exploratory-descriptive research objectives. The innovative and disruptive development of mobile technologies allows the evolution of educational models and provides the potentialization of tools for the teaching-learning of mathematics and the active role of the student in the construction of his own learning. Faced with several questions about how students learn mathematics, the following question is posed: How should a didactic software for teaching Trigonometry structured based on the constructionist theory be? In view of this, the objective of this work is to develop a theoretical-methodological proposal for teaching Mathematics through the development of an educational software. The work also presents the articulation of the Seymour Papert's Theory of Constructionism to the development of educational software for the teaching-learning of Trigonometry; the production of a script of an application for the self-learning of Trigonometry; the structuring of a didactic-pedagogical-technological proposal for the teaching-learning of Trigonometry, compatible with the possibilities of use of mobile devices. In the software development proposal, the pedagogical architecture of the game, the didactic transposition of the game, and the contributions and articulations of this proposal to the teaching of mathematics, specifically to the learning of trigonometry, are presented. The results of this research are presented in the production of a game script from the elaboration of a pedagogical plan following a learning path that results from a study developed during the production of the software. Thus, the intention is to contribute to the production of other games that have the same pedagogical objective and to build innovative tools with great potential, such as software, for the teaching of mathematics. Furthermore, the software is based on the mobile learning perspective, to favor self-study and self-learning for the student. In this way, this research tends to favor the integral formation of the student, so that in an autonomous way, he becomes the protagonist of his own learning, and above all, learns Mathematics in an interactive and dynamic way.